Monitored anaesthesia care in elderly patient - a prospective descriptional study - Al Maruf, Abdullah; Latif, Kazi Ashkar; Chowdhury, Iqbal Hossain; Kamal, Md Mustafa (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: In elderly patients for some diagnostic, therapeutic and surgical procedure, Monitored anaesthesia care (MAC) may be an anaesthetic option for them. Aim and objective: This prospective study was designed to assess the efficacy, safety, and tolerability of MAC in elderly patients. Method: This study was performed on elderly patients of both sex, age from 50 years and above, scheduled to undergo different therapeutic, diagnostic and surgical procedures. The patients characteristics, pre-anaesthetic problems, anaesthetic techniques, anaesthetic agents, anesthetic time, MAC procedure and complications were assessed. Result: They involved mainly hypertension (26.49%) and diabetes mellitus (21.78%). Almost all procedure was done under sedation (70.38%), local anaesthesia (22.71%) and under only monitoring without sedation or local anaesthesia (6.90%). There were no serious adverse events reported in any patients during MAC. The common complications were arrhythmia (9.60%), vomiting (7.36%) and desaturation (4.56%), hypertension (5.64%). Complications were minor, transient and promptly managed and corrected. MAC duration was ranged from 15 to180 minutes. The mean procedure time was 35.1 + 12.5 minutes. Majority of cases were completed within 30 minutes (51.21%). Conclusion: In properly selected elderly patients, MAC is a safe and effective method of providing intraoperative care for some common diagnostic, therapeutic, and operative procedures. DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18154 Journal of BSA, 2010; 23(1): 19-24